Harmony in The Parade of Mountainous Harvests as An Effort to Improve The Economy of The People - Toyibatussalamah, Toyibatussalamah; Nurrokhim, Isma; Mahmud, Ali (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The tradition of the harvest parade held at the Prabu Anom Tomb complex in Kediri Regency is not only a cultural and spiritual event, but also has significant socio-economic dimensions for the community. This study aims to examine the values of harmony contained in the procession and how this tradition can be a medium for improving the economy of the community. This study uses a qualitative approach with ethnographic methods. The results show that the mountain parade not only preserves local wisdom and strengthens social cohesion, but also creates a space for economic interaction, especially for small traders, MSMEs, and local tourism actors. Community participation in this activity demonstrates the synergy between religious, cultural, and economic dimensions that give rise to social harmony. Thus, the gunungan procession at the Tomb of Prabu Anom is not merely a symbol of respect for ancestral traditions, but also a strategy for community empowerment based on local wisdom that is oriented towards the economic sustainability of the community